Pengaruh Kemampuan dan Motivasi Kerja terhadap Penanganan Pasien Covid di Puskesmas Cempaka Kota Parepare - Anwar, Muh. Rafly; Haniarti, Haniarti; Putri Rusman, Ayu Dwi; Zarkasyi R, Rahmat; Amir, Rahmi (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2024)
The Covid-19 outbreak is a global disease that has spread widely and affected many people, especially medical personnel who are at the forefront of treating Covid-19 patients and are very vulnerable to contracting the Covid-19 virus because they deal with patients directly. The aim of this research is to determine the influence of work ability and motivation on the treatment of Covid patients at the Cempaka Community Health Center, Parepare City. This research is a quantitative research. The data collection uses observation and questionnaires. There were 42 respondents. Analysis of the data using descriptive and inferential statistical data analysis. Use regression to see the influence between the independent variable (X) and the dependent variable (Y), either partially (separately) or simultaneously (together). The ability variable has a positive and significant influence on the ability of health workers at the Cempae Community Health Center in Parepare City to handle Covid patients. Second, there is a positive influence on the handling of Covid patients at the Cempae Health Center in Parepare City. The variable of work motivation partially has a positive and significant effect on the handling of Covid patients at the Cempae Health Center, Parepare City. Third, the variables Ability and Work Motivation have a significant effect on the handling of Covid patients at the Cempae Health Center, Parepare City. The results of hypothesis testing or simultaneous testing explain that the variables ability (X1) and Work Motivation (X2) have a significant effect on patient handling (Y), proven based on the results of the F-count value (57.815) > F-table (3.15) and the significance value that the sig value. (0.000) < 0.05 which means the hypothesis is accepted. The results of the coefficient of determination are 0.651, that the contribution of variables that occur in the Patient Handling variable (Y) is 65.1% determined by ability (X1) and work motivation (X2), the remaining 34.9% is influenced by other variables that are unknown and not researched in this assessment.